Evolution of the concept of corporate social responsibility and ways of its development in modern Russia - A. N. Kurayev; I. G. Morozova; A. A. Grunina; N. M. Suray; M. V. Shatokhin (Омский научный вестник: Серия "Общество. История. Современность")
This article discusses the principles and current trends of corporate social responsibility, as well as the basis for the modern development paradigm. Corporate social responsibility is necessary for sustainable development of the organization and the welfare of society as a whole, as it has legal, social, ethical, environmental and philanthropic context of the functioning of the developing organization. It is defined that efficiency of corporate social responsibility of the organization is defined by positive social and ecological influence on a society. However, today many companies, including Russian ones, are only beginning to realize the importance of ESG-strategy implementation in their activities, which is one of the determining factors of competitiveness and investment attractiveness. The analysis of ESG-transformation of domestic business has been carried out. It is found that the introduction of ESG-practices in Russian business is in its infancy. The growth of digital technologies and the involvement of employees in the dissemination of ESG practices will help to accelerate the process of ESG-strategy implementation in the activities of the organization. All these factors together will create a favorable environment for corporate social responsibility reporting in Russia.